Experimental Studies on the effects of chlorpyrifos on Rats III. Haematological Findings - El-durssi, Ibrahim S. H.; El-Awami, Ifdial O.S.; Mahmoud, Ghyath S.; Benkhaial, Fahim A. (Al-Mukhtar Journal of Sciences, 2007)
This Study performed to investigate the effects of Chlorpyrifos (one of the most used insecticides) on blood pictures of rats. Thus a total of 110 male rats were used and experiment ally divided into four groups: the first group was used as control group .While the second group of rats received an oral daily doses of 1/10 LD50. The third and fourth groups of rats were administered single oral dose of 1/10 LD50 and 1/30 LD50 respectively .The median lethal dose was determined which appeared to be equal to 81.2 mg/ kg. B. W. Haematological investigations revealed an increase in white blood cell’s count (WBC), red blood cell’s count (RBC), and mean carpuscular volume (MCV). On the other hand there is a decrase in haemoglobin estimation (Hb), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC)and the total blood platelets count (PLT).